Small-tract percutaneous nephrolithotomy for an elderly female with renal and ureteral stones complicated by pyogenic kidney - Difu Fan; Leming Song; Chunxiang Luo; Monong Li; Jack Michel; Donghua Xie (Urology Case Reports, 2021)
Percutaneous nephrolithotomy (PCNL) is feasible in the extremely elderly patients. However, there were higher rate of complications and longer hospitalizations. The case presented is a 95-year-old female who was admitted to the hospital and was diagnosed with multiple stones in the right kidney and upper ureter with right renal effusion and infection, urosepsis, and chronic bronchitis. After sufficient preoperative preparation, small-tract PCNL under vacuum suctioning was performed using the left lateral position under combined lumbar spinal and epidural anesthesia. The patient recovered and was discharged smoothly on schedule. Good clinical and social effects have achieved.